dCas9-SPO11-1 locally stimulates meiotic recombination in rice - Léo Herbert; Aurore Vernet; Aurore Vernet; Julien Frouin; Julien Frouin; Anne Cécile Meunier; Anne Cécile Meunier; Jeremy Di Mattia; Minghui Wang; Gaganpreet K. Sidhu; Luc Mathis; Alain Nicolas; et al. (Frontiers in Plant Science)
IntroductionMeiotic crossovers shuffle the genetic information transmitted by the gametes. However, the potential to recover all the combinations of the parental alleles remains limited in most organisms, including plants, by the occurrence of only few crossovers per chromosome and a prominent bias in their spatial distribution. Thus, novel methods for stimulating recombination frequencies and/or modifying their location are highly desired to accelerate plant breeding. MethodsHere, we investigate the use of a dCas9-SPO11-1 fusion and clusters of 11 gRNAs to alter meiotic recombination in two chromosomal regions of a rice hybrid (KalingaIII/Kitaake). To accurately genotype rare recombinants in regions of few kbp, we improved the digital PCR-based pollen-typing method in parallel.ResultsExpression of the dCas9-SPO11-1 fusion protein under the ubiquitous ZmUbi1 promoter was obtained in leaves/anthers/meiocytes and found to complement the sterility of the Osspo11-1 mutant line. We observed a 3.27-fold increase over wild-type (p<0.001) of recombinant pollens in a transgenic hybrid line (7a) targeting a chromosome 7 region. In the offspring plant 7a1, a significant 2.05-fold increase (p=0.048) was observed in the central interval (7.2 kb) of the Chr. 7 target region. This stimulation of meiotic recombination is consistent with the expression of the dCas9-SPO11-1 fusion and gRNAs as well as with the ChIP-revealed binding of dCas9-SPO11-1 to the targeted region. In contrast, no stimulation was observed in other transgenic lines deficient in the above pre-requisite features, expressing the dCas9-SPO11-1 fusion but no gRNAs or targeting a Chr.9 region. DiscussionThese results open new avenues to locally stimulate meiotic recombination in crop genomes and paves the way for a future implementation in plant breeding programs.